(3eTGcd GdeYGedGJ GdeGdjI Hjf GdTQY hGdYQa (B/s - (3YHO Gddg, MSGf eMehOs ((3HjQhJ(B: s (3OGQ GdgGOj ddWHGYI hGdfTQ(B, s, 2008)
(3eTGcd GdeYGedGJ GdeGdjI,GdJLGQI BOGHgG heTGcdgG,GdecGSH GdeMQeI,GdHjY heTGcdg,GdELGQI,GdYed hMbhb GdYGed,GdCLQI Ydi GdhGLHGJ,GdOdGdI hGdSeSQI,GdGSJKeGQGJ GdeGdjI,GdeYGedGJ GdQHhjI,GdeRGQYI,GdQgf,GdMLQ,GdMhGdI,GdTQcI,GdeTJQcGJ,GdJCejfs
(3HHdjhZQGajG(B:(3U U(B.561-564s
Keywords: (3GdeGdjIs; (3GdeYGedGJ(B-(3abg GSdGejs